Noch so ’ne Phrase, Faust auf die Nase! – Eine phraseologische Untersuchung des Nerv-Sprech - Schulze, Florian (Linguistik Online, 2014)
Spiegel has published a web dictionary of "Nerv-Sprech"-units, which functions as a ready-made corpus. This article categorizes these phraseological units as slogans, pragmatic or predicative phrasemes. Furthermore, in order to evaluate the validity of the term "Nerv-Sprech" from the point of view of the language system, I examine whether there are semantic or structural modifying aspects that are dominant among the phrasemes (and if so, which ones). Finally, a ludic function of "Nerv-Sprech" is postulated as a result of the creativity in modifying these phrasemes.